Synchronous motors stability estimation methodologies under three-phase faults in power supply grids - A. I. Fedotov; R. E. Abdullazyanov; R. M. Mudarisov (Известия высших учебных заведений: Проблемы энергетики)
This  article  presents  the  three  phase  short  circuit  impact  on  synchronous motors stability research results. The analysis of the researches done in this field shows that they neglect following features in motor operation: the voltage sag form occurred during short circuit; dependency of voltage on the motor busbars from the currents passing in the power supply grid elements; the impact of sag through excitation system. Research conducts the voltage sag form equation for the three phase short circuits occurring in the adjacent electric lines. Synchronous motor model was developed to account the impact of neglected factors on the motor stability. Finally, article proposes the methodology developed to assess synchronous motor stability under three-phase short circuit faults occurring in power grids. Research results could be used to calibrate protective relays used in power supply grids with powerful synchronous motors.